Effect on Cuff Pressure of Various Endotracheal Tube Cuff Inflation Methods - Khan, Tanveer Ahmed; Iqbal, Muhammad Rashid; Ranjha, Chaudhry Raheel; Rukh, Mah; Bhalli, Hafiz Ahmed Hassam; Raza, Muhammad Ahmed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare mean endotracheal tube cuff pressures generated using two endotracheal tube cuff inflation methods;just-Seal versus Stethoscope-Guided in patients undergoing elective surgery under general Anaesthesia. Study Design: Quasi-experimental study. Place and Duration of Study: Anesthesia Department, Combined Military Hospital, Rawalpindi Pakistan, from Jan to Jul 2021. Methodology: A total of 100 patients undergoing elective surgery under general endotracheal tube anaesthesia between 18–60 years of age of either gender were included. Patients were equally allocated (n=50 each) to two Groups, A (Just Seal Group) and B (Stethoscope Guided Group). In the Group-A method, the air was injected until no air leak could be heard. The pressure was measured using a “Portex cuff pressure manometer”. In the Group-B method, a stethoscope bell was placed on the thyroid lamina, and harsh breath sounds were auscultated during ventilation. Cuff was inflated till the sounds changed to smooth sounds. The pressure was measured and then noted down. Results: Among 100 patients, 39 % were males, and 61 % were females. The mean endotracheal cuff pressure in Group-A was 39.90±3.19 centimetres of water and 28.42±3.52 centimetres of water, with Group-B (p-value of 0.001). Conclusion: Post-intubation cuff pressure measured in patients undergoing elective surgery under general anaesthesia of the just seal group is higher than that in the stethoscope-guided group. Keywords: Cuff pressure, Stethoscope-guided, Tracheal intubation.